Development of a Tool for the Evaluation and Emprovement of the Energy Management in Small and Medium Enterprises (SMEs) - Morales, Inés; Jiménez-Navarro, Juan-Pablo (My University, 2011)
A new tool is presented in this article. The main objective is the improvement of the small and medium companies’ energy management systems in order to obtain energy savings and the adaptation of the organizations according to the recognized standard UNE-EN 16001:2010. The application of the tool lets companies reduce their energy consumption and improve their processes in an energy efficiency perspective. The methodology is based in questionnaires and tests which will report information in order to identify all standard requirements. In a near future; the expected benefits are going to be a knowledge about the companies’ EMS situation; information to prioritize actions to improve; identification of critical areas; comparison between different EMS evaluation results (for example: company’ EMS with industry average; etc.); improve companies knowledge about energy; energy efficiency; etc.
Keywords: Recursos energéticos; Energía - Conservación; Energy; Energy Management System; Energy in SMEs